Neither Good Nor Bad : Why Human Beings Behave How They Do. - Besier, Gerhard (Cambridge Scholars Publishing, 2014)
When confronted by a range of violent actions perpetrated by lone individuals, contemporary society exhibits a constant tendency to react in terms of helpless, even perplexed horror. Seeking explanations for the apparently inexplicable, commentators often hurry to declare the perpetrators as ""evil"". This question is not restricted to individuals: history has repeatedly demonstrated how groups and even entire nations can embark on a criminal plan united by the conviction that they were fightin ...